2022
DOI: 10.3390/buildings12040390
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, Strategies, and Best Practices for BIM Adoption in Quebec Prefabrication Small and Medium-Sized Enterprises (SMEs)

Abstract: Prefabricated construction has long faced problems due to the industry’s fragmentation. Building Information Modeling (BIM) has thus appeared as an efficient solution to provide a favorable environment for efficient completion of projects. Despite its benefits, implementing BIM successfully in small and medium-sized enterprises (SMEs), which represent the vast majority of manufacturers in Quebec, requires deep risk analysis and rigorous strategies. Hence, this work aims to study BIM implementation barriers, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The use of BIM in construction projects is increasing worldwide, and the research attention towards BIM is increasing as well (Liu et al , 2022; Mahmoud et al , 2022). The review of the literature revealed that the BIM research is primarily distributed in two directions, the first is to explore the applications of BIM in various construction activities, which included identifying future potentials for BIM beyond the current known applications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of BIM in construction projects is increasing worldwide, and the research attention towards BIM is increasing as well (Liu et al , 2022; Mahmoud et al , 2022). The review of the literature revealed that the BIM research is primarily distributed in two directions, the first is to explore the applications of BIM in various construction activities, which included identifying future potentials for BIM beyond the current known applications.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarises the BIM benefits as extracted from the literature, the benefits are categorised according to the project lifecycle phases. Although the benefits and applications of BIM as described in the literature appears to be very promising, however, the literature also revealed that these benefits are not fully realised, and the applications are not all being used in the current status of the construction industry (Arrotéia et al , 2022; Deng, 2022; Mahmoud et al , 2022). There is a positive correlation between the BIM level of implementation and the extent of use within a project (Gharaibeh et al , 2022b; Oraee et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, BIM can also help the construction industry players to achieve the sustainability effort, especially the government bodies and authorities, consultants, and contractors, to successfully implement and deliver the construction project within its budgeted time, costs, and quality toward sustainable housing construction projects. BIM is ideally suited to ease project communication, especially between project professionals for carrying out design improvement and building performance analysis, thus making the construction project more efficient [13].…”
Section: Introductionmentioning
confidence: 99%